A Rasch model analysis on validation and enhancement of the operation of Integers' Diagnostic Test - Embong, Zulmaryan; Saidin, Nurhafizah (2022)
A diagnostic test named Errors Identification Integers Test (EIIT) was developed to identify students’ errors and misconceptions when solving routine problems on operations of integers. The Rasch rating scale, a one-parameter logistic item response model, has been used to enhance diagnostic test interpretation and validate its measurement properties. The diagnostic test was given to the 622 students from eight schools in four states of Peninsular Malaysia, chosen through stratified random sampling. The test consists of forty multiple choice questions. The Rasch model was found to fit the diagnostic test well: 33 out of 40 items had acceptable infit and outfit statistics, where the recommended range for multiple choice question was (0.7-1.3) and item difficulty spanned a wide range (-2.2 to 3.67 logits). The item characteristic curve offered enhanced interpretation of the diagnostic test. Data suggest that the diagnostic test is an adequate measure of errors and misconceptions in operations of integers. The Rasch model supports its validation and enhances its interpretation.